'Minding the Just Gap': Perceptions of the Legitimacy of Income Inequality from the South African Social Attitudes Survey. (2nd January 2021) - Roberts, Benjamin; Cooper, Adam; Swartz, Sharlene; Juan, Andrea
ABSTRACT: This article explores perceptions of the legitimacy of income inequality in South Africa, looking at the 'just income gap': salaries considered to be fair for occupations at opposite ends of the status continuum. Data from the 2009 and 2016 waves of the South African Social Attitudes Survey (SASAS) were analysed. Findings on perceived actual and ethical wages for five occupations indicated that, although South Africans feel that those on the low end of the wage continuum deserve a substantial increase in income, fairly high, occupationally specific levels of wage inequality were deemed legitimate. The 'just gap' was heavily influenced by perceptions of particular occupations and the 'ethical calibre' of people assumed to work in those sectors, with high public sector salaries perceived as illegitimate based on perceptions of corruption. South Africans accepted fairly high levels of inequality but favoured higher incomes for the poor and limits on corporate sector salaries.